2020
DOI: 10.1177/1098612x20959973
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of serum procalcitonin and heparin-binding protein levels as biomarkers of bacterial infection in cats

Abstract: Objectives Although bacterial infection can lead to sepsis and high mortality, early and easy diagnosis of sepsis can improve survival. In cats, the diagnosis of systemic bacterial infection is quite challenging, and, usually, non-specific markers for inflammation are employed. In humans, procalcitonin, heparin-binding protein and absolute neutrophil count are biomarkers that are studied in bacterial infections and sepsis owing to their high sensitivity and specificity. Methods A total of 56 cats were categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…Another marker that has gained increased interest for sepsis investigations in veterinary medicine is procalcitonin (PCT). Procalcitonin is synthesized in monocytes and hepatocytes as a prohormone of calcitonin in response to cytokine stimulation 112 . Bacterial infections are common in cats, and a local bacterial infection can progress to a life‐threatening condition 113,114 .…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Another marker that has gained increased interest for sepsis investigations in veterinary medicine is procalcitonin (PCT). Procalcitonin is synthesized in monocytes and hepatocytes as a prohormone of calcitonin in response to cytokine stimulation 112 . Bacterial infections are common in cats, and a local bacterial infection can progress to a life‐threatening condition 113,114 .…”
Section: Future Perspectivesmentioning
confidence: 99%
“…To date, only one study has investigated this topic, and indicated an increase in serum PCT levels in cats. 25 Likewise, serum PCT levels were higher in dogs with sepsis than in healthy controls. 24 However, viral infections were not evaluated in previous studies.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, it has been reported that the PCT level begins to increase 2 h after a lipopolysaccharide injection in dogs, increases significantly over 12 h and returns to baseline after 48 h. 24 To the best of our knowledge, infection-associated PCT production in cats has been documented in a single study, which indicated an increase in serum PCT levels during bacterial infections. 25 However, PCT’s potential correlation with viral infections, the effect of different bacterial infections on PCT production and PCT’s correlation with mortality have not been investigated in cats. Furthermore, no studies investigating the significance of PCT mRNA expression have been published.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jae-Geum Cho ve ark. (42) bakteriyel enfeksiyon geçiren kedilerde PCT ve heparin binding protein (HBP) biyobelirteç olarak değerlendirilmiş ve iki parametre arasında kıyaslama yapmışlardır. Kırk tanesi bakteri enfeksiyonu geçiren, 16 tanesi kontrol olmak üzere toplam 56 tane kediaraştırmaya dahil edilmiştir.…”
Section: Kedilerde Prokalsitoninunclassified